1999
DOI: 10.1016/s0022-5223(99)70055-3
|View full text |Cite|
|
Sign up to set email alerts
|

Studies in thoracic aortic graft infections: The development of a porcine model and a comparison of collagen-impregnated dacron grafts and cryopreserved allografts

Abstract: This novel porcine model of thoracic aortic graft infection is a reproducible method for the investigation of thoracic aortic graft infections. The phase I study investigated the timing of the induced bacteremia and the most susceptible position of a graft. Phase II demonstrated that collagen-impregnated Dacron grafts are equivalent, if not superior, to cryopreserved allografts in resisting central vascular graft infections in the ascending aorta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Nevertheless, even if the use of biological valves is gaining increased interest, there are still many patients in whom a definite surgery-for example, by use of a mechanical valve-should be striven for, especially because the commonly used argument that biological material offers better resistance against bacterial infection has been disproved in many experimental and clinical applications. [16][17][18] In our opinion, the debridement of all infected tissue is a prerequisite for the healing of the artificial material, but on the other hand, the extensive debridement leads to a considerable lack of annular tissue. This can also occur after removing a previously implanted aortic valve and/or root prosthesis in nonendocarditis cases, especially if additional extensive decalcification is necessary.…”
Section: Discussionmentioning
confidence: 98%
“…Nevertheless, even if the use of biological valves is gaining increased interest, there are still many patients in whom a definite surgery-for example, by use of a mechanical valve-should be striven for, especially because the commonly used argument that biological material offers better resistance against bacterial infection has been disproved in many experimental and clinical applications. [16][17][18] In our opinion, the debridement of all infected tissue is a prerequisite for the healing of the artificial material, but on the other hand, the extensive debridement leads to a considerable lack of annular tissue. This can also occur after removing a previously implanted aortic valve and/or root prosthesis in nonendocarditis cases, especially if additional extensive decalcification is necessary.…”
Section: Discussionmentioning
confidence: 98%
“…The allograft-related mortality rate was only 2.2% in their study, and all allograft-related deaths and complications were in patients who received fresh allografts [10]. Rowe and associates failed to demonstrate superior results of cryopreserved allografts over collagen-impregnated Dacron grafts [48]. However, a multicenter study involving 90 patients in Belgium further demonstrated that cryopreserved aortic allograft replacement is a promising technique for the management of aortic prosthetic graft infections [49].…”
Section: In Situ Allograft Replacementmentioning
confidence: 95%
“…As regards the choice of substitutes, a heart valve allograft is considered superior to the other prosthesis like mechanical valves and bioprosthetic valves. Since the 1990s, several retrospective studies have shown that possible superiority of the valve allograft use for severe infective endocarditis and prosthetic valve endocarditis cases from the clinical results [Grinda et al, 2005;Haydock et al, 1992;Leyh et al, 2004;Sabik et al, 2002;Vogt et al, 1997;Yankah et al, 2005] ; however, there is no final consensus of an allografts' potential of antimicrobial capacity due to the absence of randomized controlled studies and scientific evidence supporting this mechanism [Eichinger et al, 2002;Rowe et al, 1999], and the presence of opposing opinions [El-Hamamsy et al, 2010;Klieverik et al, 2009]. Further information was contributed in 2008 by our group to strongly support the allografts' property to overcome infection from a scientific point of view; the key substance conferring the antibacterial property was found to be indoleamine 2,3-dioxygenase (IDO) [Narui et al, 2009;Saito et al, 2008].…”
Section: Resistance Against Infectionmentioning
confidence: 99%